1999
DOI: 10.1152/jappl.1999.86.4.1101
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of factors determining oxygen uptake at the onset of exercise

Abstract: Considerable debate surrounds the issue of whether the rate of adaptation of skeletal muscle O2 consumption (QO2) at the onset of exercise is limited by 1) the inertia of intrinsic cellular metabolic signals and enzyme activation or 2) the availability of O2 to the mitochondria, as determined by an extrinsic inertia of convective and diffusive O2 transport mechanisms. This review critically examines evidence for both hypotheses and clarifies important limitations in the experimental and theoretical approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
183
2
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(194 citation statements)
references
References 99 publications
7
183
2
2
Order By: Relevance
“…The factors responsible for limiting the rate of V O 2 adaptation during the transition toward a new exercise steady-state broadly are categorized as being related to limitations imposed by 1) the adaptation of muscle blood flow and muscle O 2 delivery, and 2) the activation of muscle enzymes and provision of substrates (other than O 2 ) to the mitochondrial TCA cycle and electron transport chain (16,24,37). Hughson and Morrissey (22,23) suggested that the slower adaptation of V O 2 in the S2 compared with S1 could be a consequence of an O 2 transport limitation, as suggested by slower HR kinetics (i.e., greater HR MRT) (23).…”
Section: Discussionmentioning
confidence: 99%
“…The factors responsible for limiting the rate of V O 2 adaptation during the transition toward a new exercise steady-state broadly are categorized as being related to limitations imposed by 1) the adaptation of muscle blood flow and muscle O 2 delivery, and 2) the activation of muscle enzymes and provision of substrates (other than O 2 ) to the mitochondrial TCA cycle and electron transport chain (16,24,37). Hughson and Morrissey (22,23) suggested that the slower adaptation of V O 2 in the S2 compared with S1 could be a consequence of an O 2 transport limitation, as suggested by slower HR kinetics (i.e., greater HR MRT) (23).…”
Section: Discussionmentioning
confidence: 99%
“…37 Experimentally, Grassi et al 29 found no significant differences in response dynamics between muscle and pulmonary uptake, VO 2m and VO 2p , during the transition from light to moderate intensity exercise. The methodology used for measuring VO 2m dynamics across the femoral bed during exercise may not be sufficiently accurate because the VO 2m response depends on lumped measurements of oxygen content in the femoral vein and bulk measurements of femoral blood flow, 61 which may result in having slow muscle oxygen uptake dynamics close to that of pulmonary oxygen uptake. Several studies have considered whether the observed dynamics of oxygen uptake at the onset of exercise is the manifestation of an ''inertia'' in the rate of O 2 delivery to the muscle fibers 18 or of an intrinsic slowness of the intracellular oxidative metabolism.…”
Section: Internal and External Respirationmentioning
confidence: 99%
“…Relieving a limitation at the level of the TCA cycle may only expose other limitations (e.g. oxygen delivery, enzyme activation), which prevent enhancement of oxidative metabolism (Tschakovsky & Hughson, 1999;Gurd et al 2006). We therefore hypothesised that any glutamine-mediated enhancement of TCA cycle flux, and hence NADH & FADH production, would exacerbate the oxygen delivery limitation found during high intensity exercise (Linnarsson, Karlsson, Fagraeus & Saltin, 1974;Adams & Welch, 1980;Knight et al 1993;Hogan, Richardson & Haseler, 1999;Richardson et al 1999a;Richardson, Leigh, Wagner & Noyszewski, 1999b;Linossier et al 2000).…”
Section: Introductionmentioning
confidence: 99%